Alfabetização: dificuldades e estratégias nas práticas alfabetizadoras - DIAS, Débora Mendes (2024)
This article's main objective is to analyze literacy practices (reading and writing) in a public school in the city of Abaetetuba, in order to verify the difficulties and possibilities of strategies in the teaching and learning process. The questions that guided the research were: How is teaching pedagogical practice developed for teaching reading and writing? What are the difficulties faced in literacy work in the classroom? What strategies are created to overcome difficulties? The research has a qualitative approach and was carried out in two stages: the first stage was observations in the field school, specifically in a 2nd year elementary school class. In the second stage of the research, a period of application of didactic intervention activities was established with the aim of promoting the learning of children in the literacy process. As a theoretical reference, the following authors were used as a basis: Soares (2020), Soares (2016), Frade (2005), Marques et al. (2006), Falabelo et al (2020), Braggio (1992), Kramer (2019), Mortatti (2006), Libâneo (1990), Alves-Mazzotti and Gewandsznajder, Minayo (2007). The results of this investigation indicate that literacy practice based on traditional, rigid, mechanical, decontextualized methods, which privilege aspects of coding and decoding, presents itself as a decisive factor that can act as an obstacle, making it difficult for students to learn. In this way, we believe in the process of literacy and literacy having the text as the central axis for the learning process, as it is a more attractive and motivating proposal, in addition to being a practice that is concerned with material, social and linguistic aspects. for the construction of significant knowledge by the student.